STRATEGI GURU DALAM MENJAGA STABILITAS EMOSI SAAT MENGHADAPI SISWA KELAS II YANG KURANG KOOPERATIF - Sarita Wardhani, Zefanya; Adilla Desy Rizbudiani; Andreas Erwin Prasetya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The issue of uncooperative student behavior in lower-grade classroom presents a significant challenge for teachers in creating a conducive learning environment. This study aims to describe the forms of uncooperative behavior among students, the strategies employed by teachers to address such behavior, and the efforts made by teachers to manage their emotions during the learning process. A descriptive qualitative approach was applied, involving second-greade teachers from an elementary school in the Special Region of Yogyakarta. Data were collected through interviews and observations, then analyzed using the interactive model of Miles and Huberman. The findings reveal that teacher’s emotional regulation skill, implemented throough a behavioristic approach and supported by a positive school environment an collegial collaboration, play a crucial role in managing uncooperative student behavior and fostering a productive, harmonious classroom atmosphere.